Anti-angiogenic activities of methanol extracts of imbao (Anodontia edentula) using chorioallantoic membrane assay - Domaub, Nour Adel P.; Coronel, Kimverly Hazel I.; Solon, Christine Cherry E.; Moneva, Carlo Stephen O. (2024)
Angiogenesis is a physiological process with a role in vessel proliferation that is significant
in tumor development. Inhibition of this process is called anti-angiogenesis, employing the
use of various natural medical agents. These include mollusks, which are deemed as a source of different medicinal compounds that can act as anti-angiogenesis treatments utilized in cancer therapy. This study aims to investigate different concentrations of methanol extracts of a molluscan marine bivalve, Anodontia edentula, and determine the anti-angiogenic
activity of the extract using chorioallantoicmembrane (CAM) assay. By utilizing vessel
count analysis, results show A. edentula extracts exhibit anti-angiogenic activity, with
negative values in percent growth and positive values in percent inhibition. Two out of
four concentrations of extracts (1000 and 500 ppm) exhibit no significant difference with
positive control (ibuprofen) regarding its anti-angiogenic ability. It is highly recommended to
investigate the compounds responsible for the angiogenic inhibition observed in A. edentula.
Keywords: Blood-vessels—Growth; Angiogenesis; Mollusks